Given
n → ∞ lim ( n 2 + 5 7 n − 2 − n ) = q p
for coprime positive integers p , q , find p + q .
This is a part of the College Calc problem set. You can find more problems here .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The function n 2 + 5 7 n − 2 − n can be rewritten as ( n + 1 0 7 ) 2 − 2 . 4 9 − n using the completing the square method. As n approaches infinity, the ( n + 1 0 7 ) 2 term in the square root predominates meaning lim n → ∞ ( n + 1 0 7 ) 2 − 2 . 4 9 = n + 1 0 7 . The final limit is thus lim n → ∞ ( n + 1 0 7 − n ) = 1 0 7 and p + q = 1 7
Rewrite the limit as: n → ∞ lim ( n 1 + 5 n 7 − n 2 2 − n ) = n → ∞ lim ( n ( 1 + 5 n 7 − 1 ) )
as the 2 / n 2 term is negligible.
Using the negative binomial expansion , ( 1 + x ) 1 / 2 ≈ 1 + 2 1 x − 2 1 2 − 1 ⋅ 2 ! 1 x 2 . Substituting x = 5 n 7 :
= n → ∞ lim ( n ( 1 + 2 1 5 n 7 + 8 1 ( 5 n ) 2 7 2 − 1 ) ) = n → ∞ lim ( n ( 2 1 5 n 7 ) ) = 1 0 7
so p + q = 1 7 .
Y = n 2 + 5 7 n − 2 − n
Y = n ( 1 + 5 n 7 − n 2 2 − 1 )
Here n reaches to ∞
Y = n ( ( 1 + 1 0 n 7 − n 2 1 ) − 1 )
Using property when x reaches to 1 + x = 1 + 2 x
Y = n ( 1 0 n 7 − n 2 1 )
Y = 1 0 7 − n 1
Here n 1 reaches to zero
So Y = 1 0 7
Finally p + q = 1 7
L = n → ∞ lim ( n 2 + 5 7 n − 2 − n ) = n → ∞ lim n 2 + 5 7 n − 2 + n ( n 2 + 5 7 n − 2 − n ) ( n 2 + 5 7 n − 2 + n ) = n → ∞ lim n 2 + 5 7 n − 2 + n 5 7 n − 2 = n → ∞ lim 1 + 5 n 7 − n 2 2 + 1 5 7 − n 2 = 1 0 7 Divide up and down by n
Therefore p + q = 7 + 1 0 = 1 7 .
n → ∞ lim ( n 2 + 5 7 n − 2 − n ) = n → ∞ lim n ( 1 + 5 n 7 − n 2 2 − 1 ) = n → ∞ lim n ( 1 + 2 1 [ 5 n 7 − n 2 2 ] − 1 ) using 1 + x = 1 + 2 1 x + ⋯ = 1 0 7
giving the answer 1 7 .
Problem Loading...
Note Loading...
Set Loading...
Let us prove the general formula:
n → ∞ lim ( a n 2 + b n + c − a n 2 + b ′ n + c ′ ) = 2 a b − b ′
We multiply the numerator and denominator by a n 2 + b n + c + a n 2 + b ′ n + c ′ such that we have
n → ∞ lim a n 2 + b n + c + a n 2 + b ′ n + c ′ ( a n 2 + b n + c − a n 2 + b ′ n + c ′ ) ( a n 2 + b n + c + a n 2 + b ′ n + c ′ ) = n → ∞ lim a n 2 + b n + c + a n 2 + b ′ n + c ′ ( b − b ′ ) n + c − c ′ .
Notice, that the denominator can be replaced by 2 a n and the numerator by ( b − b ′ ) n . Then,
⋯ = n → ∞ lim 2 a n ( b − b ′ ) n = 2 a b − b ′ . □
Substituting the values a = 1 , b = 5 7 , c = − 2 , b ′ = 0 , c ′ = 0 , we have
⋯ = 2 1 5 7 − 0 = 1 0 7 .
Hence p + q = 7 + 1 0 = 1 7 .